Running dictation strategy and listening comprehension, among superior basic students, at a public school in Loja, during the 2023 – 2024 school year. - Quisatasig Capa, Richard Javier (2024)
The English language every day becomes a necessary tool for global social, political and work interaction, hence the importance of listening comprehension skills from basic higher education. Therefore, the present study manages to identify the effectiveness of dictation strategies for improving listening comprehension skills in basic higher education students of a public school in the city of Loja during the 2023 - 2024 school period. Using initial diagnosis and evaluation after the intervention carried out, that is, pre-test and post-test, the effectiveness of the proposed strategies was quantitatively measured; On the other hand, through the implementation of a perception questionnaire, it is possible to identify the general perception of the students to the implementation of listening comprehension strategies in superior basic students. The results obtained through descriptive statistics manage to identify improvements in the students' general scores in the understanding of main ideas, improvement by 0.10 points, vocabulary comprehension by 0.28 points and understanding of details by 2.32 points; being a positive change in the final general averages that reach 2.70 in the general average. On the other hand, the general perception is positive, improving interest in the subject and as a result improving school performance and listening comprehension skills. Finally, the study concludes that the effectiveness of the implementation of dictation strategies to improve listening comprehension is positive in 75% of cases, where the minimum required values are reached and exceeded. Keywords: Listening, running dictation, English language, language learning.